Pengaruh Komitmen Organisasi Dan Pengawasan Terhadap Disiplin Pegawai Melalui Kepuasan Kerja Sebagai Variabel Intervening (Studi pada Koperasi Simpan Pinjam Makmur Mandiri Cabang Kota Tangerang) - Sutedi, Sutedi; Prahiawan, Wawan; Nupus, Hayati (Jurnal Riset Bisnis dan Manajemen Tirtayasa, 2021)
The purpose of this study is to examine the effect of organizational commitment and supervision on employee discipline through job satisfaction as an intervening variable. The object of the research is the employees of the Tangerang City Branch Makmur Mandiri Savings and Loan Cooperative. The number of samples taken was 54 people with saturated census or sampling techniques. Analysis of research data using the student version of the SEM-PLS method. The results showed that there was no effect of organizational commitment on work discipline; There is a positive and significant effect of supervision on work discipline; There is a positive and significant influence between organizational commitment on job satisfaction; There is a positive and significant influence between supervision on job satisfaction; and There is a positive and significant influence between job satisfaction on work discipline.